A Pragmatic, Randomized Clinical Trial of Gestational Diabetes Screening. Issue 8 (August 2021) - Hillier, Teresa A.; Pedula, Kathryn L.; Ogasawara, Keith K.; Vesco, Kimberly K.; Oshiro, Caryn E. S.; Lubarsky, Suzanne L.; Van Marter, Jan
Abstract : (Abstracted from N Engl J Med 2021;384:895–904) Gestational diabetes mellitus (GDM) affects up to 25% of pregnant women and increases the risk of a number of adverse maternal and neonatal outcomes. There are 2 screening approaches for GDM: 1-step screening preferred by the American Diabetes Association and 2-step screening recommended by the American College of Obstetricians and Gynecologists.